2014
DOI: 10.5539/ijbm.v9n7p87
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Organizational Citizenship Behavior for Job Performance and the Moderating Role of Human Capital

Abstract: This study aims to investigate the relationship between organizational citizenship behavior directed toward individuals (OCBI) and the organization (OCBO), and job performance. In addition, the moderating role of experiential/intelligential human capital on the above relationship was also examined. Data was collected from 585 R&D engineer supervisor-subordinate dyads currently employed at high-tech companies. OCBI and OCBO were found to be positively related to job performance. In addition, an engineer's exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 47 publications
4
26
0
4
Order By: Relevance
“…The extant literature mainly focused on the relationship between each IA component and OCB ( Avey et al., 2011 ; Bolino et al., 2002 ; Chow, 2009 ; Kang and Snell, 2009 ; Luthans et al., 2007 ; Ng and Feldman, 2010 ; Norman et al., 2010 ; Wei, 2014 ; Wright and McMahan, 2011 ). Thus, we highlight below each component of IA and its relationship with OCB, based on which we propose the study model: Human capital in general terms is about employee knowledge, skill, abilities, and experiences as internal resources for organizations ( Ployhart and Moliterno, 2011 ).…”
Section: Intangible Assets and Ocb Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…The extant literature mainly focused on the relationship between each IA component and OCB ( Avey et al., 2011 ; Bolino et al., 2002 ; Chow, 2009 ; Kang and Snell, 2009 ; Luthans et al., 2007 ; Ng and Feldman, 2010 ; Norman et al., 2010 ; Wei, 2014 ; Wright and McMahan, 2011 ). Thus, we highlight below each component of IA and its relationship with OCB, based on which we propose the study model: Human capital in general terms is about employee knowledge, skill, abilities, and experiences as internal resources for organizations ( Ployhart and Moliterno, 2011 ).…”
Section: Intangible Assets and Ocb Relationshipmentioning
confidence: 99%
“…These characteristics of employees are related to extra-role behaviors. First Wei (2014) showed the importance of the relationship between OCB and human capital for organizational performance, and earlier researchers had shown that human capital affects OCB ( Wright and McMahan, 2011 ; Ng and Feldman, 2010 ). However, it is important to understand whether this relationship is direct or moderated by other factors ( Garavan and McGuire, 2001 ).…”
Section: Intangible Assets and Ocb Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the organizational literature highlight the benefits of OCBs. Among others, it has been found that employee engagement in OCBs may increase knowledge sharing and job performance [23,24]. Other authors claim that OCBs exhibited by workers enhance team and group cohesiveness and contribute to overall organizational performance [2,23,[25][26][27].…”
Section: Organizational Citizenship Behaviormentioning
confidence: 99%
“…OCB refers to "individual behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate promotes the effective functioning of the organization" (Organ, 1988, p. 4). Research has found that individual engagement in OCB can increase knowledge sharing and job performance (Lin, 2008;Wei, 2014), enhance team and group cohesiveness (Lin and Peng, 2010;, contribute to the overall effectiveness of management and the organization Rego and Cunha, 2008), and consequently improve both the financial and non-financial performance of firms (Koys, 2006;Organ, 1990;Ryan, 2002). Without OCB, a work group may not be able to achieve its performance goals, and the organization may lose its competitive advantage.…”
Section: Introductionmentioning
confidence: 99%